The encyclopedia of yachting - Johnson, Peter (Dorling Kindersley, 1989)
This detailed reference book covers all aspects of yachting, from the history of the sport to the contemporary classes of yacht and dinghy. Accounts of inshore and offshore racing are highlighted with descriptions of important UK and international events and competitions. A section at the beginning of the book traces the development of yachting, describing the earliest regattas, races and pioneer voyages. Original archive photographs illustrate this historical survey up to the present day, charting the courses of the most remarkable single-handed circumnavigations and ocean crossings. The chapters on inshore and offshore racing describe the most important events in a yachtsman's calendar - from dingy sailing and sailboard racing, to round-the-world events, all with race details and results. The Americas Cup and Olympic Games are given extra coverage in their own chapters. A fully illustrated A-Z section features 216 national and international yacht and dinghy classes, giving key facts on design specifications and the history of each class. This is followed by a chapter on the construction and design of racing and cruising yachts. A photographic guide to yacht construction materials and equipment shows the technological improvements that have been made in recent years. A special section at the back of the book describes the most popular sailing areas of the world, with maps illustrating the major yachting ports that are used as bases for cruising and racing.